The cost of capital in emerging markets (2014)
I applied nine methods already proposed in the literature to calculate the cost of equity of companies from the six largest stock markets in Latin America, included in the MSCI emerging markets list. A number of these methods modify the discount rate obtained using the standard Capital Asset Pricing Model (CAPM) by adjusting for country risk premiums. I found a strong correlation between the results yielded by a number of these methods. I then applied an econometric test based on categorical variables to determine whether the estimated cost of equity is influenced by country and industry effects. I found that industry effects are more important than country effects in Latin America. This work gives empirical evidence for specific country and industry determinants of the cost of equity that are not explicitly treated in the extant literature. Then, I examine the determinants of the spread between corporate and sovereign debt yields. I use data of corporate bonds in fifteen emerging markets in order to calculate the spread between their yield to maturity and the respective sovereign debt yield to maturity for each of these markets. I found the determinants of such spread, controlling for debt term structure, and other variables. Additionally, I found industry and country effects not explained by variables at firm, issue, country, or international levels. The contribution of this work is to point out that industry effects are more important than country effects in explaining the spread, even when controlling by country and industry specific factors